Pengaruh Kapasitansi Plasma Kapasitor dan Putaran Mesin Terhadap Konsumsi Bahan Bakar Mesin 125 CC - Akhlis Nur Firman Ardiansyah Santoso; Santoso Santoso (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The ignition system is an important system in a vehicle. Currently, the level of emissions produced by vehicles continues to increase every year. This can be caused by high fuel consumption values. The solution to this is to improve the quality of the spark plug by adding a capacitor to the ignition/ignition capacitor. The way the Plasma Capacitor Igniton works is by adding a high voltage non-polar capacitor which is connected in parallel to the output coil. The experimental method will be carried out using quantitative methods. By installing ignition plasma capacitors with different capacitor sizes of 1.5 mF (STD), 440 pF, 660 pF installed in parallel with the spark plug wires with variations in engine speed running from 1500 – 5500 rpm to check emissions. To check the fuel consumption value for Rpm 4500 - 9500 which has been adjusted previously. Fuel Consumption Test Results The use of 440 pF capacitors generally provides an increase in SFC efficiency at most engine speeds, with the largest percentage reduction at RPM 5500 (22.64%). The use of 660 pF capacitors shows varying results. At some RPMs, such as 5500, the SFC actually increases (3.77%), while at other RPMs such as 6500, it shows a significant decrease (27.66%).